Microplastics are associated with elevated atherosclerotic risk and increased vascular complexity in acute coronary syndrome patients - Yang, Yunxiao; Zhang, Feng; Jiang, Zhili; Du, Zhiyong; Liu, Sheng; Zhang, Ming; Jin, Yanyan; Qin, Yanwen; Yang, Xiubin; Wang, Chenggang; Gao, Hai (Particle and fibre toxicology, 2024)
Microplastics, widely present in the environment, are implicated in disease pathogenesis through oxidative stress and immune modulation. Prevailing research, primarily based on animal and cell studies, falls short in elucidating microplastics' impact on human cardiovascular health. This cross-sectional study detected blood microplastic concentrations in patients presenting with chest pain using pyrolysis-gas chromatography/mass spectrometry and evaluating inflammatory and immune markers through flow cytometry, to explore the potential effects of microplastic on acute coronary syndrome. The study included 101 participants, comprising 19 controls and 82 acute coronary syndrome cases. Notably, acute coronary syndrome patients exhibited elevated microplastic concentrations, with those suffering from acute myocardial infarction presenting higher loads compared to those with unstable angina. Furthermore, patients at intermediate to high risk of coronary artery disease displayed significantly higher microplastic accumulations than their low-risk counterparts. A significant relationship was observed between increased microplastic levels and enhanced IL-6 and IL-12p70 contents, alongside elevated B lymphocyte and natural killer cell counts. These results suggest an association between microplastics and both vascular pathology complexity and immunoinflammatory response in acute coronary syndrome, underscoring the critical need for targeted research to delineate the mechanisms of this association. 1 Blood microplastic levels escalate from angiographic patency, to angina patients, peaking in myocardial infarction patients. 2 Microplastics in acute coronary syndrome patients are predominantly PE, followed by PVC, PS, and PP. 3 Microplastics may induce immune cell-associated inflammatory responses in acute coronary syndrome patients.